2019
DOI: 10.1039/c8cp06539j
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nanoparticles on the excitation energies of the photochromic dihydroazulene/vinylheptafulvene system

Abstract: This paper studies how nanoparticles affect photochromic systems, focusing on the influence of gold nanoparticles on the optical properties of the dihydroazulene/vinylheptafulvene (DHA/VHF) system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Earlier, it was investigated how solvation affects the storage energies and thermal back reaction barriers, 18 and we have also studied the effects of nanoparticles on the storage properties and kinetics of the DHA/VHF couple. 19,20 Consequently, we wish to expand upon the knowledge available on the thermal back reaction of MOST systems, since it is crucial to their applicability. We have chosen to study three different NBD/QC derivatives, the parent-DHA/VHF system, and a 3-amino-substituted-DHA/VHF system for which the structures and relevant reaction schemes are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, it was investigated how solvation affects the storage energies and thermal back reaction barriers, 18 and we have also studied the effects of nanoparticles on the storage properties and kinetics of the DHA/VHF couple. 19,20 Consequently, we wish to expand upon the knowledge available on the thermal back reaction of MOST systems, since it is crucial to their applicability. We have chosen to study three different NBD/QC derivatives, the parent-DHA/VHF system, and a 3-amino-substituted-DHA/VHF system for which the structures and relevant reaction schemes are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, we found that the NPs can enhance both one and two photon absorption of these systems while also providing significant redshifts in the absorption and clear alterations in the electric properties. [19][20][21] Hence, the coupling of such NPs to the NBD/QC system could be used as catalyst for the thermal back reaction while also possible tuning optical properties for solar energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The theoretical modeling of systems of such an intrinsic complexity requires a multiscale description, which is able to capture the individual and collective behavior of the composite system. Focusing on the molecular nanoplasmonics, 8,[21][22][23][24][25][26][27][28] the requirement of a multiscale hybrid approach arises naturally: the small subsystem, i.e., the single molecule or the molecular aggregate, and the larger component, i.e., the nanostructure, need to be described by means of different approaches. The level of description is adapted according to the different size and level of accuracy required/affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid methods for molecular plasmonics can be categorized based on the level of theory for the molecular target and on the description of the plasmonic nanostructure. Considering the molecular target, we can distinguish three main categories, ordered in terms of increasing complexity: (i) classical polarizable point dipole models ("dip" in the rest of this work), 22,[29][30][31][32][33][34] where the molecule is characterized only by using a frequency-dependent polarizability tensor (often isotropic); (ii) two-level quantum mechanical models ("2lev" from now on), a model derived from quantum optics where the molecule is described as a quantum system with two states (ground and excited), 7 separated by a certain excitation energy and coupled through a transition dipole, possibly obtained from empirical data; (iii) fully atomistic models based on a quantum-chemistry description ("QM," to comply with the standard acronyms of hybrid quantumchemistry models), 2,6,11,12,[24][25][26][27][28][35][36][37][38][39][40][41][42][43][44][45][46] providing chemical details and predictive power. The present classification is somewhat rough, and, in particular, for polaritonic chemistry, the 2lev model has been extended to include the dependence on one or a few nuclear coordinates to model photochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation